Attitude and Behavior of Maternal Health Care Providers During Child Birth in a Tertiary Care Hospital in Karachi - Zaira Batool, Sumbul Sohail, Shabnum Shameem Asim, Shaista Rashid, Zubaida Masood, Hadya Qadri, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Pakistan is among the most populous countries of South East Asia with very high maternal mortality rate. One of the reasons of this elevated maternal mortality is non-availability of skilled workers at the time of labour. Objective: The study was carried out to see the frequency of abuse and disrespect during childbirth at a public sector hospital of Karachi and whether it affects their choice regarding the place of delivery in future pregnancy or not? Methodology: A cross sectional study was done after ethical review board approval and consent. A prevalidated questionnaire was used to collect the data from 476 women after their delivery but before they get discharged from the heath facility. Descriptive statistics were calculated and Univariate and multivariate analysis was done using spss 25. Result: Out of 466 patients, 401 (86%) reported some kind of disrespect and abuse from health care providers. Around 60% responded that they were not introduced to the health provider while 30% complained regarding the lack of involvement during and before the procedure. Almost 25% participants complained that no barrier was used to cover them during the procedure. Conclusion: Given study revealed that the occurrence of non-dignified maternity care is frequent in the area studied. Hospital administration and health policy makers should make sure and reinforce the training of health personnel who exhibit non dignified behavior towards laboring woman. This will help in reducing the maternal humiliation and psychological trauma of vulnerable women in public sector hospitals. Moreover maternal health will also improve as more women will attend health care facility for labour and delivery.